Causal Relationship Between Economic Growth, Unemployment, Poverty and The Impact to Human Development Index (HDI) 2010 - 2016 - Aida, Nur; Siti Khumairoh, Nur (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research is to know the correlation between economic growth and unemployment to poverty and, on the other hand, to know the correlation between economic growth (Asfia, 2016), unemployment, and poverty to the Human Development Index (HDI) as an intervening variable. This research is quantitative research, and the data used is secondary data from BPS for 2010-2016. Analyze tools used in this research, which are multiplier linear regression, correlation, and path analysis. The independent variable is economic growth and unemployment; the dependent variable is poverty and the human development index. Correlation economic growth and unemployment to poverty is quite strong, which is R = 0.974 and R² = 0.948. nwhile, Correlation between economic growth, unemployment, and poverty to human development index (HDI) is quite strong, which is R = 0.965 and R² = 1.  The poverty variable is not a mediating variable between economic growth and HDI because the direct effect of economic growth on HDI is greater than the indirect effect of economic growth on HDI through poverty and this is supported by the Sobel test, where the Sobel Test value is 0.66704791 below the 1.96 threshold. The poverty variable is not a mediating variable between unemployment and HDI because the direct effect of unemployment on HDI is greater than the indirect effect of unemployment on HDI through poverty and this is supported by the Sobel test, where the Sobel Test value is 1.03759856 below the 1.96 threshold.